Safety incidents in family medicine. Issue 12 (5th September 2011) - O'Beirne, Maeve; Sterling, Pam D; Zwicker, Karen; Hebert, Philip; Norton, Peter G
Abstract : Objective: To discuss the characteristics of incidents reported to the Medical Safety in Community Practice (MSCP) safety learning system. Methods: Members of family physician offices in the Alberta Health Services—Calgary zone, confidentially reported patient safety incidents via web or fax from September 2007 to August 2010. The incident reporting form contained both open-ended and closed questions. Incidents were reviewed for their characteristics. Results: A total of 19 family practices participated in MSCP. A total of 264 useable reports were collected. Reporting was higher when practices first joined and then decreased. There was an average of 1.4 reports per month. Physicians submitted the majority of reports. Physicians and nurses were more likely to report an incident than office staff. The vast majority of reported incidents were judged to have ' virtually certain evidence of preventability' (93%). Harm was associated with 50% of incidents. Only 1% of the incidents had a severe impact. The top four types of incidents reported were documentation (41.4%), medication (29.7%), clinical administration (18.7%) and clinical process (17.5%). Conclusion: MSCP has developed and implemented the first safety learning system in Canada for family practice. All clinic members were encouraged to submit reports, but most of the incidents were reported by physicians. The vast majority of incidents reported were preventable with limited severity. The most frequently reported types of incidents fell into the categories of documentation and medication. The low reporting rates suggest that for family practices incident reporting may not be the most effective method to determine the types and frequency of incidents in family medicine.